Two new species of Stenatkina Young, 1986 from China with comparative notes on the female genitalia (Hemiptera: Cicadellidae: Cicadellini) - Meng, Ze-Hong; Yang, Mao-Fa; Li, Zi-Zhong (Zootaxa, 2012)
Stenatkina Young, 1986 is a sharpshooter genus that includes six species, three of them recorded from China. In this paper, twonew species, S. moliensis sp. nov. and S. luteimacula sp. nov. are added. A key is given to distinguish all species of the genus.Descriptions and illustrations of the male and female genitalia of the new species and of other Chinese species are provided. S.heveli Young is newly recorded from China. Comparative notes on the female genitalia within Stenatkina are provided. The preliminary results show that the female genitalia provide useful features for distinguishing Stenatkina species.